2019
DOI: 10.5296/ijl.v11i1.14259
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse Devices in English Scientific Research Articles Written by Native and Non- Native Speakers of English

Abstract: The present study examined the frequently used metadiscourse devices in English scientific research articles written by native (English researchers) and non-native (Arab English researcher) and sought to determine whether differences exist in the use of these devices between Arab researchers of scientific research articles and Native English researchers of scientific research articles. Data was collected from forty research scientific articles written and published in international journals and Arab journals; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This finding seems to match with the findings obtained by Hyland and Milton (1997), who found that non-native writers had problems in expressing certainty, which is likely due to their lacking knowledge of the effective use of the interactional devices such as stance markers. This finding also conforms to what has been concluded by Al-Zubeiry (2019) and Darwish (2019), who asserted that non-native writers of English use less interactional devices than their native counterparts.…”
Section: Analysis Of Stance-marking Of Interaction Across Disciplinessupporting
confidence: 92%
See 1 more Smart Citation
“…This finding seems to match with the findings obtained by Hyland and Milton (1997), who found that non-native writers had problems in expressing certainty, which is likely due to their lacking knowledge of the effective use of the interactional devices such as stance markers. This finding also conforms to what has been concluded by Al-Zubeiry (2019) and Darwish (2019), who asserted that non-native writers of English use less interactional devices than their native counterparts.…”
Section: Analysis Of Stance-marking Of Interaction Across Disciplinessupporting
confidence: 92%
“…A number of research studies have been done in exploring and investigating writer's stance-marking of interaction in different genres and fields and across disciplines, languages, and cultures, such as research on Saudi EFL academic writing (Al-Zubeiry, 2019;Al-Zumor, 2021), academic writing (Babaii et al, 2015;Bunton, 1999;Darwish, 2019;Hyland, 2004), journal author guidelines (Hyland & Milton, 1997;Messabhia, 2020;Moini & Salami, 2015), book reviews (Nayernia & Ashouri, 2019), research articles (Qomariana & Soetama, 2021), and doctoral dissertation and Master's theses (Sayah & Hashemi, 2014;Taymaz, 2021). For the convenience of presentation and the limitation of the current study, we attempt to review the most relevant studies to better understand related literature.…”
Section: Studies On Writer's Stance-marking Of Interactionmentioning
confidence: 99%
“…Some of these studies emphasized the cross-cultural and cross-linguistic variations of metadiscourse (e.g. ; Sultan 2011; Lee & Casal 2014;Alshahrani 2015;Al-Al-Zubeiry 2019) and some others examined the cross-disciplinary variations (e.g., Zarei & Mansoori 2011;Cao & Hu 2014;Estaji & Vafaeimehr 2015;Khedri & Konstantinos 2018;Kashiha & Marandi 2019). Metadiscourse was also examined within the abstract section (e.g., Gillaerts & Van de Velde 2010; Khedri, Heng & Ebrahimi 2013, Alotaibi 2015, introduction and methods sections (e.g., Jalilifar & Kabezade 2012;Loi & Lim 2013;Khedri & Konstantinos 2018;Cao & Hu 2022) as well as conclusion and discussion sections (e.g., Mirshamsi & Allami 2013;Ghahremani & Biria, 2017;Liu & Buckingham 2018).…”
Section: Previous Related Literaturementioning
confidence: 99%
“…Yet, despite all efforts, effective and applicable incorporation of given to new topic information flow into tertiary-level writing instruction is still scarce (He, 2020). Accordingly, training NNES writing teachers to identify and assess the flow of given to new topic information in academic writing, and having them adjust the grade weighting associated with given to new topic information flow, can assist in focusing on the intelligibility of communicative competence skills within writing assessments (Al-Zubeiry, 2019;Arabi & Ali, 2015;Fitriati & Yonata, 2017;Jones, 2015;Strauss & Feiz, 2013).…”
Section: Introductionmentioning
confidence: 99%